Manganese dioxide‐graphene nanocomposite film modified electrode as a sensitive voltammetric sensor of indomethacin detection. (1st August 2016) - Liu, Yuxia; Zhang, Zhenfa; Zhang, Cuizong; Huang, Wei; Liang, Caiyun; Peng, Jinyun
Abstract : Excess amount of analgesic and anti‐inflammatory drug, such as indomethacin, often leads to serious gastrointestinal complications; therefore, amount of such active compound should be regulated in commercial drugs. This study proposes an efficient analytical technique to detect indomethacin selectively. We prepared and investigated electrochemical properties of a manganese dioxide‐graphene nanocomposite film modified glassy carbon electrode (MnO2 ‐Gr/GCE). The behavior of the modified electrode as electrocatalyst towards indomethacin oxidation was also examined. The cyclic voltammetric results reveal that the electrocatalytic activity for the oxidation of indomethacin can significantly be enhanced on the MnO2 ‐Gr/GCE. Indomethacin exhibited a sensitive anodic peak at about 0.90 V at MnO2 ‐Gr/GCE. The data obtained from differential pulse voltammetry showed that the anodic peak currents were linearly dependent on the indomethacin concentrations in the range of 1.0 × 10 −7 to 2.5 × 10 −5 mol/L with a detection limit of 3.2 × 10 −8 mol/L ( S / N = 3). Most importantly, the proposed method shows efficient and selective sensing of indomethacin in commercial pharmaceutical formulations. This is the first report of a voltammetric sensor for indomethacin using MnO2 ‐Gr/GCE. We believe that this new method can be commercialized for routine applications in laboratories. Abstract :